State Standards & Opportunity to Learn in New Jersey - Firestone et al, William A.; Camili, Gregory; Yurecko, Michelle; Monfils, Lora; Mayrowetz, David (Education Policy Analysis Archives, 2000)
A survey of 245 New Jersey teachers provides a baseline for examining how the introduction of state standards and assessments affects the teaching of math and science in the 4th grade. These policies are promoting teaching of additional topics in both areas. The changes in the delivery of professional development have not yet been sufficient to lead to substantial changes in instructional practice. While inequities in access to material that characterized the state in the early 1990s have diminished, we find a pattern of inquiry-oriented science teaching more prevalent in wealthy districts and teaching to the test more prevalent in poorer ones. We also note some areas where middle-income districts appear disadvantaged.